2021
DOI: 10.2147/ijgm.s335266
|View full text |Cite
|
Sign up to set email alerts
|

Using Immune-Related lncRNA Signature for Prognosis and Response to Immunotherapy in Cutaneous Melanoma

Abstract: Background: Cutaneous melanoma is a highly malignant skin tumor, and most patients have a poor prognosis. In recent years, immunotherapy has assumed an important role in the treatment of advanced cutaneous melanoma, but only a small percentage of patients benefit from immunotherapy. A growing number of studies have demonstrated that the prognosis of patients with cutaneous melanoma is closely related to long non-coding RNA and the tumor immune microenvironment. Methods: We downloaded RNA expression data and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 51 publications
2
11
0
Order By: Relevance
“…In addition, Wang et al have identified eight immune-related lncRNAs with prognostic value in melanoma dataset. Among them, MIR205HG expression is associated with the poor outcome of patient and its expression is positively correlated with the expressions of immune checkpoints like PD-1, CTLA4, LAG3, and TIM3 in adenocarcinoma and melanoma ( 51 ). Our present study demonstrates that immunology-related pathway including innate and adaptive immune response were among the most significantly-enriched biological processes of dys-regulated lncRNAs in primary melanoma, implying that dys-regulated lncRNAs may participate in the regulation of anti-tumor immunity and inflammatory responses during melanoma progression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Wang et al have identified eight immune-related lncRNAs with prognostic value in melanoma dataset. Among them, MIR205HG expression is associated with the poor outcome of patient and its expression is positively correlated with the expressions of immune checkpoints like PD-1, CTLA4, LAG3, and TIM3 in adenocarcinoma and melanoma ( 51 ). Our present study demonstrates that immunology-related pathway including innate and adaptive immune response were among the most significantly-enriched biological processes of dys-regulated lncRNAs in primary melanoma, implying that dys-regulated lncRNAs may participate in the regulation of anti-tumor immunity and inflammatory responses during melanoma progression.…”
Section: Discussionmentioning
confidence: 99%
“…With increasing interests in lncRNAs' function in the development of human disease, a huge number of studies have established corresponding ceRNA networks in colon cancer and dug out differently expressed genes, including lncRNAs, correlated with the clinical prognosis and disease development [13][14][15][16]. The abnormal expression of USP30-AS1 has been widely reported, such as in cervical cancer, glioblastoma, ovarian cancer, bladder urothelial carcinoma, and cutaneous melanoma [17][18][19][20][21]. The dysregulation of USP30-AS1 was observed in a lncRNA expression profile of colorectal cancer [8].…”
Section: Discussionmentioning
confidence: 99%
“…It could play a role as a potential biomarker of neuroblastoma (Prajapati et al, 2019). AC026369.3 (Wan et al, 2021), LINC01871 (Chen Q. et al, 2020;He and Wang, 2020;Ma et al, 2020), USP30-AS1 (Chen P. et al, 2020;Xue et al, 2021), and AC093297.2 could become potential prognostic biomarkers for various malignant tumors in bioinformatics approaches.…”
Section: Discussionmentioning
confidence: 99%